Modeling carbon stock change and carbon dioxide emissions under different ecosystems in the Brazos River Basin, USA - Birhan Getachew Tikuye; Ram Lakhan Ray; Sanjita Gurau (Environmental Challenges)
Anthropogenic activities, including land-use change, industrialization, fossil fuel combustion, agriculture practices, and livestock management, drive significant greenhouse gas (GHG) emissions, particularly CO₂, CH₄, and N₂O. This study aims to assess carbon stock changes and emissions across different ecosystems within the Brazos River Basin, Texas, USA. Land use and land cover (LULC) data were derived from the National Land Cover Database (NLCD), offering a spatial resolution of 30 meters. Biomass carbon density data, both above- and below-ground, were acquired from the Distributed Active Archive Center (DAAC), while soil organic carbon (SOC) data (0–30 cm depth) were obtained from global SOC databases. The Integrated Valuation of Ecosyst. Serv. and Trade-offs (InVEST) model was employed to estimate carbon stock changes, using a carbon stock difference approach to quantify changes between 2001 and 2021. Results reveal increasing water areas, built-up zones, barren lands, shrublands, herbaceous regions, agriculture, and wetlands, while forested and pasture areas decreased from 2001 to 2021. Specifically, barren lands, shrublands, and agricultural zones functioned as carbon sinks, sequestering 70,637.2, 678,313.7, and 652,036.7 tons of CO₂ annually, highlighting their role in atmospheric carbon mitigation. The overall net emission trend of 923,336.5 tons of CO₂ annually highlights the urgent need for strategic land management interventions such as afforestation, reforestation, soil conservation, wetland restoration, and sustainable grazing practices that enhance carbon storage, particularly in forested and pasture regions. Additional investigation into adaptive land-use strategies and conservation initiatives is crucial for strengthening sustainable ecosystem functions and reducing future emissions.